Management Information System Fertiliser Projects - Planning Commission (Planning Commission)
This document is a description of the Management Information System which has been developed for use in monitoring the construction of now fertiliser projects throughout the country. Initiated at the instance of the Minister of Petr ileum and Chemicals, the system covers all aspects of the preconstruction and construction phases of fertiliser project development in both the private and public industries. The major emphasis of the information system, however, is placed in monitoring the progress of construction of the public sector fertiliser plants.
Prepared For: the Ministry of Petroleum and Chemicals Government of India the Management and Project Evaluation Division Committee on Plan Projects Planning Commission Government of India